Strategy for colorimetric and reversible recognition of strong acid in solution, solid, and dyed fabric conditions: Substitution of aminophenoxy groups to phthalocyanine - Huang, Qianqian; Hye Lee, Eun; Oh, Byeong M.; Chun, Hye W.; Lee, Woosung; Kim, Jong H. (Spectrochimica Acta - Part A: Molecular and Biomolecular Spectroscopy, 2022)
A series of novel peripherally tetra- and octa-substituted copper phthalocyanines (CuPcs) bearing various aminophenoxy groups was designed and synthesized for detecting strong Brønsted acids. Octa-(diethyl-aminophenoxy)-substituted CuPc 5 exhibited excellent HCl detection capability with high sensitivity (limit of detection: 240 ppb), rapid (<2s), and selectivity for strong acids in versatile conditions including solution, solid, and dyed fabric. Furthermore, CuPc 5 noted reusability in recyclable tests with HCl and NH3, demonstrating its great potential for practical detection of HCl and ammonia gas leak under various environments. Based on systemic characterizations based on UV–Vis absorption spectra and NMR, we suggest that the proton of HCl associated with the N atom of CuPc 5, and the proton sensing abilities are directly related to the dissociation constants of the amine groups. The steric hindrance of alkyl chains and molar absorption coefficient of the CuPc species in THF solvent, as well as the H2O content of the solvent system, also affected the sensing performance. Due to less bulky nature of diethyl-amino groups having higher pKa and stronger basicity, CuPc 5 featured effective recognition of strong acids with pKa value less than −2.0 (Ka > 100). To the best of our knowledge, this is the first demonstration of pKa-sensitive colorimetric chemosensor using CuPc backbone, in particular for distinguishing strong Brønsted acids such as HCl.
Keywords: Chemo-sensors; Condition; Copper phthalocyanine; Copper-phthalocyanine; Detection capability; Dyed fabrics; Gas detection; Reversible chemosensor; Strongest acid; Synthesised; Colorimetry; Coloring Agents; Isoindoles; Protons; Solvents; Copper phthalocyanines; Gas detection; Hydrogen chloride; Reversible chemosensor